2001
DOI: 10.1023/a:1010714715534
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examined the relationship between the domains of environmental factors, family illegal drug use, parental child-rearing practices, maternal and adolescent personality attributes, and adolescent illegal drug use. A nonclinical sample of 2,837 Colombian youths and their mothers were interviewed about intrapersonal, interpersonal, and environmental factors in their lives. Results indicated that certain environmental factors (e.g., violence, drug availability, and machismo), family drug use, a distant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…It is notable that the predictive role of maternal factors (maternal rules in particular) did not come out as strongly in this study as in studies in the U.S. Interestingly, this same finding has been observed in studies that have applied FIT in Colombia (South America; e.g. Brook et al, 2001). Colombia and South Africa are both middle income countries and likely to be more similar socio-economically to each other than to the US.…”
Section: Discussionsupporting
confidence: 79%
“…It is notable that the predictive role of maternal factors (maternal rules in particular) did not come out as strongly in this study as in studies in the U.S. Interestingly, this same finding has been observed in studies that have applied FIT in Colombia (South America; e.g. Brook et al, 2001). Colombia and South Africa are both middle income countries and likely to be more similar socio-economically to each other than to the US.…”
Section: Discussionsupporting
confidence: 79%
“…Gottfredson and Koper (1996) argue for research that includes broader culturally significant contextual factors, such as neighborhood problems and the availability of substances, to understand the influences on alcohol use for different ethnic groups. Broader community influences (e.g., neighborhood climate, drug availability) have been found to significantly influence alcohol, other substance use, and related problems across ethnicities (Brook et al, 2001; Duncan, Duncan, & Strycker, 2002). The present study offers evidence that the neighborhood is an important influence for alcohol use among both African-American and White youth, who increasingly perceived that alcohol was easy to access in their neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a prospective study of 1,400 rural 6th graders, Sullivan et al (2004) found that family support and parental monitoring buffered the relation between witnessing community violence and alcohol and drug use. In the broader literature on adolescent substance use that is not specific to violence exposure, monitoring (Chilcoat & Anthony, 1996;Chilcoat & Breslau, 1999;Flannery, Williams, & Vazsonyi, 1999;Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Li, Stanton, & Feigelman, 2000;Mounts, 2001;Svensson, 2000), parental responsiveness (Bogenschneider, Wu, Raffaelli, & Tsay, 1998), mother-adolescent bonding or attachment to parents (Bahr, Maughan, Marcos, & Li, 1998;Brook et al, 2001;Corwyn & Benda, 2000), parental support (Corwyn & Benda, 2000;Marshall & Chassin, 2000;Piko, 2000;Sullivan et al, 2004), family cohesion (Dakof, 2000), and low or no family substance use (Brook et al, 2001) is linked to lower adolescent substance use.…”
mentioning
confidence: 99%